2017
DOI: 10.1126/science.aam9550
|View full text |Cite
|
Sign up to set email alerts
|

Response to Comment on “Density functional theory is straying from the path toward the exact functional”

Abstract: Kepp argues in his Comment, among other concerns, that the atomic densities we have considered are not relevant to molecular bonding. However, this does not change the main conclusion of our study, that unconstrained fitting of flexible functional forms can make a density functional more interpolative but less widely predictive.K epp argues in his Comment (1) that our Report (2) does not properly assess the accuracy of approximate functionals for molecules. Many studies have been published to assess the accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 14 publications
3
53
0
Order By: Relevance
“…Medvedev et al (26,27) concluded that (i) functionals constructed with little or no empiricism tend to produce more accurate electron densities than highly empirical ones; (ii) at the level of little or no empiricism, the accuracy of the density tends to increase along with the complexity of the DFA as one ascends the Jacob's ladder from LDA to GGA to meta-GGA to hybrids; and (iii) recent DFAs on average are shifting away from the exact functional.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Medvedev et al (26,27) concluded that (i) functionals constructed with little or no empiricism tend to produce more accurate electron densities than highly empirical ones; (ii) at the level of little or no empiricism, the accuracy of the density tends to increase along with the complexity of the DFA as one ascends the Jacob's ladder from LDA to GGA to meta-GGA to hybrids; and (iii) recent DFAs on average are shifting away from the exact functional.…”
Section: Resultsmentioning
confidence: 99%
“…As energy and density are two sides of one coin, the exact functional shall yield the exact energy of the system from its exact density. Such a mismatch between energy and density suggests a departure from the exact functional (26,27). This argument adds to the long-standing debate on how DFAs can be improved.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Since atoms are the basic building block of molecules, a number of popular density functionals have been parametrized using ab initio data on noble gas atoms; these functionals have been used in turn as the starting point for the development of other functionals. A comparison of the results of density‐functional calculations to accurate ab initio data on atoms has, however, recently sparked controversy on the accuracy of a number of recently published, commonly used density functionals . This underlines that there is still room for improvement in DFT even for the relatively simple case of atomic studies.…”
Section: Introductionmentioning
confidence: 99%
“…[], and for a recent debate, see Refs. []), we believe that databases will undoubtedly remain a fundamental tool for the assessment of the applicability, accuracy, and reliability of new and existing xc functionals in the years to come, regardless of the underlying wars between optimization philosophies (from first principle vs. parametrized). It is objectively true that more parameters in the xc functionals require more data in the training set (a statistical necessity to avoid over‐training), but the availability of larger training sets does not necessarily translate into more parametrized functionals, nor into more parameters in a functional …”
Section: Introductionmentioning
confidence: 99%